Bis(trimethylphenylammonium) hexa[bromido/chlorido(0.792/0.208)]stannate(IV) - Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
In the title molecular salt, [C(6)H(5)(CH(3))(3)N](2)[SnBr(4.75)Cl(1.25)], the Sn(IV) atom (site symmetry (1) over bar) adopts an octahedral coordination geometry. The Br and Cl atoms are disordered over three sites in 0.7415 (13): 0.2585 (14), 0.8514 (14): 0.1486 (14) and 0.7821 (14): 0.2179 (14) ratios.